A Theoretical Study on the Fluorescence Signal Sensing of a colorimetric ClO‐ chemosensor. (20th January 2020) - Bai, Tianxin; Chu, Tianshu
Abstract: Detection of reactive oxygen species by optical signal sensing is of great interesting to the chemical and medical world. In this paper, the fluorescence signal sensing process of a colorimetric ClO ‐ chemosensor (S‐BODIPY ) has been investigated through DFT/TDDFT calculations. The relative free energy (ΔG = 23.46 kcal/mol) suggests that the oxidation process of the chemosensor by the analyte would have a favorable reaction rate, accounting for a rapid response speed, and the large binding energy of 35.3 kcal/mol supports a good selectivity of the chemosensor for ClO ‐ . The calculated vertical excitation energies of S‐BODIPY (1.93 eV) and its oxidation product SO‐BODIPY (2.01 eV) agree well with the experimental emission data (2.00 and 2.11 eV, respectively). The absorption spectra and 1 H NMR spectra have also been computed and analyzed showing reasonably good agreement with experimental ones. The fluorescence signal sensing mechanism is verified to be associated with the intramolecular charge transfer (ICT), that is, the relatively weak ICT process in SO‐BODIPY than that in S‐BODIPY has caused the observable blueshift in both the absorption and emission spectra after the detection of ClO ‐ . Abstract : An ICT mechanism isvalidated for the ClO‐ triggered reaction‐based chemosensor.PS ‐ .